Demand side analysis of microlending markets in Germany - Alexander S. Kritikos; Christoph Kneiding; Claas Christian Germelmann (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
In developing and transition economies, microlending has become an effective instrument for providing micro businesses with the necessary financial resources to launch operations. In the industrialized countries, with their highly developed banking systems, however, there has been ongoing debate on the question of whether an uncovered demand for microlending services exists. The present pilot study explores customer preferences for microlending products in Germany. Among the interviewed business owners, 15% reported revolving funding needs and an interest in microloans. We find that potential recipients of microloan products are retail business owners, foreign business owners, and persons who had previously received private loans. Furthermore, financial products should feature rapid access to short-term loans.
Keywords: G21; D12; M31; 330; Entrepreneurship; Microlending; Market Research; Mikrofinanzierung; Nachfrage; Unternehmer; Kreditmarkt; Deutschland